Environmental Initiatives within Canadian Christianity: Exploring Obstacles and Opportunities - Siegrist, Anthony (Université d'Ottawa / University of Ottawa, 2022)
This qualitative study adds to our understanding of the obstacles and opportunities experienced by Canadian, Christian organizations relative to their engagement in environmental initiatives. The core of this inquiry was comprised of sixteen in-depth, semi-structured interviews conducted with representatives of denominations and humanitarian agencies. Interview questions and the initial coding categories were drawn from the findings of an auto-ethnographic study by Haluza-Delay (2008). The wider relevance of Haluza-Delay’s findings was explored by engaging a broader population and by using a more consistent methodology. While this study largely confirmed Haluza-Delay’s description of the obstacles and opportunities facing Christian organizations relative to their engagement in environmental initiatives, it also identified an additional set of issues. Political polarization and shrinking resources, previously unidentified barriers, were evident in the data gathered. Occasions to hear from new voices, especially those of indigenous persons and individuals from the global South, were previously unidentified opportunities. Finally, this study found that several of the Canadian, Christian organizations represented by interviewees were undergoing a transition in their understanding of Christian mission, thereby creating new possibilities for environmental engagement.
Keywords: religion and ecology; religion and environment